Escolas do campo no Município de São Luis do Curu: limites e desafios da gestão democrática - Teixeira, Antônio Braz (2019)
This research aims to investigate the extent to which school management practices in two rural schools located in the municipality of São Luís do Curu / CE are consistent with the educational laws on Democratic Management. The research also seeks to focus on the particularities of this management within the scope of the specifics concerning the Education of the Field, having as central object the following public schools of the field of the mentioned municipality: School of Basic Education Assis Herculano, located in the locality of Caraúbas, and School of Education Basic Alonso Herculano, located in the locality of Escócio. It is therefore sought to investigate the management and the extent to which its practices are in line with the educational laws on Democratic Management in Field Education in the schools mentioned above. In order to prove the hypotheses raised in the course of this research, our study will seek theoretical support in Arroyo's works (2007, 2008, 2011); Paro (2001); Ferreira, (1999); Libane (2008), Saviani (1984, 1985); Caldart (2004, 2012); Vendramini (2013); Lima (1998, 2018); Martins (2004, 2009), among others. The methodological aspects adopted here were based on qualitative research using its own procedures (observations, case studies), as well as documentary research. Given the various issues raised throughout this work, in relation to the fact that the schools of São Luís do Curu analyzed develop democratic management, we conclude that in part, for historical and socio-cultural factors, the Pedagogical Political Projects analyzed do not point directly to a practice especially because such projects do not address the specificities of assisted communities.